Management of the Sexually Abusive/Harassing Actions of Inmates Directed Towards Correctional Staff: The Impact of Policy and Training Upon Exposure and the Corrections Workplace Culture. Issue 6 (1st November 2020) - Jones, Susan J.; Cathcart, Katy; Cooksey, Sarah
Abstract: This research study examined data obtained from the One Voice corrections organization to identify the existence of policy and training regarding sexually abusive/harassing behaviors by inmates directed at corrections staff. The data revealed that when corrections employees were aware of a policy prohibiting sexually abusive/harassing behaviors of inmate's, corrections employees reported a decreased frequency of exposure to these behaviors. The presence of a training program that addressed specific strategies was not found to reduce exposure to these types of incidents. This study found that while this type of exposure occurs for both male and female corrections employees and both male and female inmates are perpetrators, female employees report increased levels of exposure and female employees were more likely to report exposure to specific comments in their workplace regarding the sexually abusive/harassing behaviors by male inmates.